High-throughput screening of E3 ubiquitin ligases identifies TRIM48 as a novel negative regulator of RIG-I signaling - Wu, Guandi; Frankish, Jamie; Willemsen, Joschka; Ricken, Dominik; Becker, Jonas; Schweinoch, Darius; Beneke, Jürgen; Wüst, Sandra; Beil, Nina; Matula, Petr; Rohr, Karl; Erfle, Holger; et al. (Cellular signalling, 2025)
The retinoic acid-inducible gene-I (RIG-I) signaling is crucial for cell-intrinsic innate antiviral immunity. Upon cytosolic detection of virus-associated RNA, it triggers a cascade inducing production of potent cytokines, mainly type I and III interferons (IFNs). While effective, dysregulated responses can harm the host, requiring tight pathway control. Here, we performed a comprehensive, systematic siRNA-based high-throughput screen across 616 established and putative E3 ubiquitin ligases for their impact on RIG-I signaling. We employed a fluorescence-based live-cell imaging assay in A549 cells to monitor nuclear translocation of IRF3 and NF-κB, two key transcription factors downstream of RIG-I. Candidate genes were validated in an orthogonal secondary screen, assessing their impact on the functional antiviral response to a Rift Valley Fever reporter virus. Fourteen hits showed consistent effects on RIG-I signaling across both screens. These genes were further validated and characterized by assessing IFN-β promoter reporter activity and IFNB1 mRNA levels upon dsRNA transfection. TRIM48 emerged as a highly robust negative regulator. Overexpression of TRIM48 suppressed RIG-I-mediated activation of IRF3 and NF-κB, reduced IFN and IFN-stimulated gene expression, and enhanced viral replication. Conversely, TRIM48 deficiency enhanced RIG-I signaling and inhibited viral replication. Notably, TRIM48 acts as an induced feedback regulator upon infection, and its effect depended on its enzymatic ubiquitin ligase activity. Our high-throughput screen provides an unbiased assessment of close to all E3 ubiquitin ligases for their regulatory effect in RIG-I signaling, and identified several interesting candidates for further investigation. TRIM48 was established as a negative feedback regulator of the RIG-I pathway.